Мethodical approaches to human resources management in innovative enterprises - Leszczynski, V.P (Ways to Improve Construction Efficiency, 2020)
The article substantiates the theoretical and methodological provisions and practical recommendations for the human resources management system in innovative enterprises. The peculiarities of an innovative enterprise are determined, the main methods of evaluation and recruitment are researched and classified, taking into account modern requirements for creativity and innovation. It is substantiated that economic transformations have significantly changed the status of the organization as the main link in the production of material goods or the provision of various services. The market puts the organization in a new relationship with government agencies, with production and other business partners, directly with employees. New economic and legal regulators are being established, relations between the manager and subordinates are changing, between employees within the organization. Due to this, the requirements for human resource management are growing, where the human factor becomes the main factor of production. Human resource management includes all aspects related to the workforce: management, employers, workers, students, professionals. As labor markets have become more competitive, human resources professionals are now designed to provide people management techniques that not only support the institution's priorities but also ensure success in the global market. Institutions also strive to create an employment brand that resonates with specific employees. Institutions of all sizes and all industries are increasingly recognizing the importance of people. Managers and economists have traditionally seen human resource management as a mandatory expense rather than a source of value for their organizations. Economic value is usually associated with capital - equipment, technology and technical means. The limit for business expansion is not only the availability of financial capital, but also access to talent - human capital. Thus, people are crucial to organizational success, and the human and intellectual capital of the organization's staff provides an opportunity for significant competitive advantage. The content of the concept of "profitability of talents" is substantiated, the components of strategic management of human resources of the enterprise are investigated. The key characteristics and features of human resources management as a factor in supporting the growth of innovative development of the enterprise are summarized.